Evaluation of Enterprise University Website Service Quality using E-Servqual and IPA Methods - Valen Zidana Erlita; Dwi Indriyanti, Aries (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The Enterprise University Website is an academic platform for internship students and employees at PT Petrokimia Gresik. This study aims to measure user satisfaction with the Enterprise University website and identify priority improvements using the e-Servqual and IPA methods. The e-Servqual method is applied through seven dimensions: Efficiency, System Availability, Fulfillment, Privacy, Responsiveness, Compensation, and Contact. Based on these, service indicators that should be the main focus for improvement are determined using the Importance-Performance Analysis (IPA) method. This research is a quantitative study. The sample consists of 49 Merdeka internship students at PT Petrokimia Gresik who are also users of the Enterprise University website. The results show that based on e-Servqual calculations, the overall average gap between user perceptions and expectations is (-0.61). This indicates that the service quality of the Enterprise University website is still lacking and does not provide user satisfaction. Furthermore, data analysis using the IPA method, as shown in the Cartesian diagram, reveals that the top improvement priorities lie in three indicators located in Quadrant I. The findings of this study can serve as a basis for strategic decision-making by platform managers to optimize services and enhance user satisfaction in the academic processes at PT Petrokimia Gresik.